Determination of phytochemical contents of Avena sativa (oat) and its impact on Debaryomyces hansenii - ErecevIt, Pinar; KIrba?, Sevda; Zengin, Fikriye (National Academy of Sciences, India, 2014)
In the present study fatty acids, vitamins, phytosterol, flavonoid and resveratrol contents and antimicrobial activities of Avena sativa (oat) extracts treated with Debaryomyces hansenii were determined and compared. Avena sativa is consumed as the fibrous food worldwide. It was shown that total fatty acids and vitamin contents increased significantly in A. sativa extracts prepared with D. hansenii. However, the flavonoid contents decreased at different rates. It was also observed that quercetin and flavonoids were present in the extracts that contained D. hansenii. It was noted that A. sativa had changing rates of antioxidants and antimicrobial activities. Thus, it was concluded that A. sativa has an important place in a healthy lifestyle and oats have positive effect on the development of D. hansenii which is also accepted as a probiotic microorganism. This yeast developed in extracts obtained from this fibrous plant and affected the bioactive compounds at changing rates. © 2013 The National Academy of Sciences, India.
Keywords: Debaryomyces hansenii; Fatty acids; Oat; Phytosterol; Vitamins